Exploring local business opportunities: Enterpreneurship training to foster sustainable and resilient ventures di Angkatan Belia Islam-Permai Pulau Penang - Andi Mappatompo; S. Sukmawati; A. Ifayani Haanurat; Wa Ode Rayyani; Asri Jaya; Azizah Saban; Wahyudi Malik; Meily Meliyani (Universitas Muhammadiyah Malang, 2025)
development of small and medium enterprises, particularly among the children of migrant workers. However, there remains a gap in understanding and entrepreneurial skills among the youth, which poses a challenge in creating sustainable and resilient ventures. This activity aims to provide entrepreneurship training that empowers the youth from the Angkatan Belia Islam-PERMAI to recognize and leverage local business opportunities. The methods used in this activity include interactive training sessions, case studies, and group discussions, designed to enhance participants' knowledge and entrepreneurial skills. The results of this activity indicate that participants experienced an increase in their understanding of entrepreneurial concepts and were able to identify business opportunities that fit the local context. Additionally, this activity also strengthened the social networks among participants, which is expected to support the development of their businesses in the future. Thus, this training contributes to the creation of more sustainable and resilient ventures among migrant youth in Penang.